A gyorshadtest hazahozatala a frontról, 1941 őszén - Olasz, Lajos (Közép-Európai Közlemények, 2024)
In the war against the Soviet Union in 1941, the Carpathian Group and the Mobil Corps participated on the Hungarian side. After the initial battles, the Carpathian Group performed occupying tasks. The Mobil Corps fought on the front line all the way and reached the Donec River (2,200 kilometres from Budapest). In addition to the strong Soviet resistance, the long distances, the difficult terrain, the extreme weather, and the technical problems also caused great obstacles. The commander of the Carpathian Group, General Szombathelyi, urged the repatriation of the troops already in August. However, Chief of Staff General Werth and the German leadership insisted on the further participation of Hungarian forces. On September 6, Szombathelyi became the head of the Hungarian General Staff and negotiated the return of the Hungarian troops. However, the Germans only allowed the Carpathian Group and the Mobil Corps to return home, when in exchange new Hungarian occupying brigades arrived in Ukraine. The Mobil Corps could only return home at the beginning of December. During the fighting, the Mobil Corps lost most of its mechanized combat equipment.